An Application of Video Recording Technology to Enhance the Key Leader Engagement Performance at SWCS - Burgess, Tim Guy (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
In this study, video recording technology was introduced into a classroom of military students to enhance Key Leader Engagement (KLE) performance. The main objective of this study was to determine the effectiveness of using video recording technology in improving the students' level of performance in the Special Forces Warrant Officer Technical and Tactical Certification at the U.S. Army Special Warfare Center and School. All students were required to participate in several practical exercises that were designed to give each student practice at participating in a KLE. For all students, each iteration of the KLE practical exercises was video recorded and scored. A quasi-experimental study using the video recording technology was used to collect data on each student's Key Leader Engagement performance. This research also incorporated a qualitative survey to determine the students' perspectives concerning the use and effectiveness of the video recording technology during KLE training. Data from the quasi- experiment was analyzed using a paired t-test. Results revealed that the use of the video recording technology made a positively significant difference from one performance of the KLE to the next, demonstrating that video recording technology employment in improving students' level of performance between iterations of KLEs was effective. The survey results show that majority of the participants think that the use of the SPOTLITE video recording technology during the After Action Review (AAR)/Counseling session helped them to become aware of their actions during each Key Leader Engagement (KLE), that the use of the SPOTLITE video recording technology during the After Action Review (AAR)/Counseling session helped them to improve their skills during a Key Leader Engagement (KLE), and that the SPOTLITE video recording technology was used correctly/effectively.